Effects of some common bacterial fish diseases on fish behavior in aquaculture: a Review - Karga, Mustafa (Zenodo, 2025)
Aquaculture is of increasing importance and economic value in global food production. Sustainability and productivity of aquaculture are directly related to the health of the fish farmed. Bacterial diseases in fish are common in the aquaculture sector and cause significant economic losses. Therefore, it is of substantial to understand the agents, prevalence and effects of bacterial diseases on fish health. Fish behavior is an important indicator of their health status. Behavioral changes can be an early sign of disease and therefore careful observation is vital for timely diagnosis and control of diseases. This review discusses common bacterial fish diseases, their agents and specific behavioral changes observed in infected fish. In addition, potential mechanisms by which bacterial infections affect fish behavior are examined.
Keywords: fish health; Behavioral change; disease indicators; fish farming